Das Klima der Nordhalbkugel zur Zeit des Inlandeisaufbaus zwischen etwa 35000 und 25000 vor heute - Frenzel, Burkhard (ERDKUNDE, 1992)
The climatic conditions existing just before the inland ice masses and mountain glaciers advanced, which later on formed the Late Wisconsian, Upper Würmian moraine system, are discussed controversially. In general it is held that in Siberia at that time warm and moist interglacial climates favoured a strong northward expansion of the boreal forests to the present-day tundra zone, whereas in other regions, such as North America, inland ice masses are considered to have already existed. An attempt is presented here to reconstruct the climate of the Northern Hemisphere for the time between approximately 35 000 to 25000 years B.P. (I4C-ages), using a wealth of data from the broad geological, geomorphological and paleoecological literature. The period mentioned was climatically complicated. A precise dating was not possible due to the repeated difficulties in the I4C-datings of that time. Thus only interstadial conditions were used here without relying on more or less exact datings. Evidently no moist and warm climates existed at that time, neither in the Northern Hemisphere in general nor in Siberia. On the contrary, the climate was colder than today all over the Northern Hemisphere, most of all in the more northerly latitudes. There existed a strong moisture gradient from very moist conditions in subtropical and tropical zones to extremely dry climates in present-day temperate and boreal to arctic zones. Sea ice seems to have covered the North Atlantic much more intensively at that time than it does today, and strong westerly winds seem to have brought moisture to the northwestern parts of the continents. In North America and perhaps in Scandinavia, too, inland ice masses already existed at that time.